ECONOMIC IMPACTS OF ENVIRONMENTAL DEVASTATION: FISHING CRISIS IN JURUJUBA - NITERÓI/RJ - Costa Soares, Maria Teresa (2013)
This article results of research carried out at the Jurujuba’s fishing community, which was the basis for a Master’s essay. In that locus, local fishermen used to apply the know-how passed from parent to offspring in their fishing activities which was important for sustainable exploitation of natural resources. Nowadays, due to many changes, those fishermen pursue other occupations as way of living. Based on quantitative data collected from socio-economic questionnaires applied and analysis of interviews carried out, a map was designed of the characteristics related to economic aspects of labour and income in that community, and the subjective way the group perceives the crisis on fishing activity and the dissolution process of their identity. On the country’s unemployment contexture, the crisis on fishing activity at Jurujuba creates a situation in which the work group once tied down now pushes up a number of disqualified urban jobs, contributing to the unemployment rate increase.